Penerapan Asuhan Keperawatan Kepada Pasien Dengan Fraktur Tibia Di Ruang Dewasa RSUD Maren Hi. Noho Renuat Kota Tual - Yerry Soumokil; Siti Rochmaedah; Riada Ohoirenan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Fracture is a break in bone continuity as a result of a collision or blunt trauma from a certain object. Treatment of fractures can be surgical or splinting, including immobilization, reduction and rehabilitation. Fractures require immediate and appropriate treatment, because inaccurate or incorrect handling will result in further complications, such as infection, nerve and blood vessel damage, to further soft tissue damage. The most common cause of fractures is accidents, be it work accidents, traffic accidents and so on